Cellulose/BaTiO3 nanofiber dielectric films with enhanced energy density by interface modification with poly(dopamine). (1st December 2020) - Yin, Yanan; Zhang, Chenggang; Chen, Jisi; Yu, Wenchao; Shi, Zhuqun; Xiong, Chuanxi; Yang, Quanling
Highlights: PDA modification improved interaction between BaTiO3 nanofiber and cellulose. RC/PDA@BTNF films possessed improved dielectric constant and breakdown strength. The composite films exhibited high energy density, cycle stability and efficiency. The composite films maintained good dielectric properties for a long time. Abstract: Flexible electrostatic capacitors have many potential applications in modern electric power systems. In this study, flexible cellulose-based dielectric films were prepared by compositing regenerated cellulose (RC) and one-dimensional BaTiO3 nanofiber (BTNF) via a simple and environmentally friendly process. To improve compatibility and distributional homogeneity of the fillers/matrix, BTNF was surface modified by dopamine to prepare the poly(dopamine) modified BTNF (PDA@BTNF). The obtained RC/PDA@BTNF composite films (RC-PDA@BTNF) possessed higher dielectric constant and breakdown strength than those of the RC and RC/BTNF composite films. In particular, RC/PDA@BTNF composite films with 2 vol% PDA@BTNF (RC-2PDA@BTNF) exhibited a high discharged energy density of 17.1 J/cm 3 at 520 MV/m, which exceeded 40 % compared with that of RC-2BTNF at 460 MV/m. Meanwhile, RC-2PDA@BTNF could continuously work for more than 10, 000 times with a high efficiency of 91 %. Furthermore, the composite films could maintain good dielectric properties for a long time when stored in vacuum condition (under 0.3 atm). Therefore, these flexible cellulose-based dielectric materials are promising in the field of novel high-performance film dielectric capacitors.